Efforts to Improve Islamic Education Learning Achievement with the Problem Based Learning Model at SMA Negeri 1 Peureulak - Junaidi; Rosita, Riza; Nurasiah (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to improve student learning outcomes in Islamic religious education learning using problem-based learning. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subject of this study is junior high school students. The data of this study was obtained by test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with research success indicators. The results of the study show that problem-based learning can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completeness in each cycle with details of 40.19% in the pre-cycle, 69.27% in the first cycle and 87.90% in the second cycle. Thus, the use of problem-based learning can be used as an alternative to improve student learning outcomes in Islamic religious education learning.